2021
DOI: 10.2147/amep.s333223
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Contamination of Mobile Phones and Mobile Phone Hygiene of Final-Year Medical Students in Uganda: A Need for Educational Intervention

Abstract: Introduction: Contaminated mobile phones act as reservoirs for organisms causing hospital-acquired infections (HAI). Little is known about medical school students' awareness of infection prevention and control (IPC) regarding mobile phone use among medical students. We demonstrated the presence of organisms on mobile phones of final-year medical students at Makerere University College of Health Sciences and evaluated their awareness of IPC regarding mobile phone hygiene and use in a hospital setting. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
2
3
0
Order By: Relevance
“…This may be related to the constant emphasis on the importance of HAI control in recent years in China. Similar to other reports [ 19 , 24 ], most HCWs wiped their mobile phone surfaces with alcohol. On one hand, alcohol is simple, cheap, easy to get, and will not damage their phones.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This may be related to the constant emphasis on the importance of HAI control in recent years in China. Similar to other reports [ 19 , 24 ], most HCWs wiped their mobile phone surfaces with alcohol. On one hand, alcohol is simple, cheap, easy to get, and will not damage their phones.…”
Section: Discussionsupporting
confidence: 83%
“…This cross-sectional study was conducted from April to June in 24 hospitals of Chongqing, China. Sample size was calculated based on a previous similar study [ 19 ]. We used the formula N = P (1− P )/ d 2 , where N = sample size, Z α/2 = statistic for the level of confidence = 1.96, α = 0.05, P = expected prevalence = 50% (prevalence of mobile phone contamination with bacteria) [ 16 ], and d = allowable error = 0.1(10%).…”
Section: Methodsmentioning
confidence: 99%
“…Also, CONS are normal commensals of the skin and mucous membranes of humans and their species have emerged as the most common cause of healthcare-associated bloodstream infections (BSIs) for many years (Asaad et al, 2016). Also, the study revealed that the highest level of contamination in female's cellphones samples (77.6%) in general compared with males (22.38%) and showed a significantly different (Table 3); this is similar to the finding obtained by Heyba et al (2015) and Lubwama et al (2021).…”
Section: Prevalence Of Other Organismssupporting
confidence: 80%
“…Additionally, abundant isolates of S. aureus, CONS and Gram-positive bacilli from cellphones of medical students. Therefore, training programs at an early stage in medical schools on guidelines about restricting the use of cellphones in the clinical environment must be implemented (Ibrahim and Elshafie, 2016;Zakai et al, 2016;Lubwama et al, 2021). Hence the present study was carried out to screen the mobile phone of healthcare workers, which can act as a source of infection by methicillin-resistant S. aureus.…”
Section: Introductionmentioning
confidence: 99%
“…In hospitals, MPs are widely used by healthcare workers (HCWs) and students of healthcare professions within and outside hospital wards, both as personal communication devices and useful tools for clinical practice [5][6][7][8]. This could reasonably produce an Life 2023, 13, 1349 2 of 14 increased occurrence and transmission of healthcare-associated infections (HAIs) considering that they are potential carriers of microorganisms [2,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%